ChemInform Abstract: Glycerol: A Solvent and a Building Block of Choice for Microwave and Ultrasound Irradiation Procedures. Issue 20 (20th May 2014) - Cintas, P.; Tagliapietra, S.; Calcio Gaudino, E.; Palmisano, G.; Cravotto, G.
Abstract Review: 35 refs.